The comic isomorphic physics series of vibrations and waves to increase the learning interest of junior high school students - Desy Kumala Sari; Vinsensia Melania Wea; Mitra Rahayu; Pri Ariadi Cahya Dinata (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2021)
Independent learning needs to be supported by independent learning media so that student's interest in learning is increasing.Low interest in physics at junior high school level causes students to be indolent to learn.Therefore, supporting learning media are needed that can foster students' interest in learning physics. This research focuses on developing a product in the form of an isomorphic physics comic for the Vibration and Waves series which is an independent learning media. This study uses the DDDE development model, namely the stages of decide, design, develop, and evaluate. Following the development stage used in this study, it carried out a feasibility and effectiveness test. The results of the feasibility test analysis using SBi (ideal standard deviation) obtained an average score of 85 which was interpreted into the product quality criteria in the "Very Good" category. Furthermore, the effectiveness test was carried out by testing on a small scale, and then the results were analyzed using simple statistics to obtain the results that 91.7% of students expressed "interest" in learning to use "isomorphic physics" comics. Thus, the use of " the isomorphic physics" comic series Vibration and Waves in physics learning at the junior high school level can increase students' interest in learning.